The Effect of Renal Transplantation on Respiratory Muscle Strength in Patients with End Stage Renal Disease - Tavana, Sasan (Tanaffos, 2016)
BACKGROUND: There is evidence of musculoskeletal and respiratory involvement in patients with chronic kidney disease (CKD). This is attributed to protein calorie imbalance that is caused by the disease process, and hemodialysis and is generally referred to as uremic myopathy. This results in calcification of respiratory muscles such as diaphragm and intercostal muscles. There are limited data about respiratory muscle strength in patients with CKD. We intended to evaluate the effect of kidney transplantation on respiratory muscles strength in patients with CKD. MATERIALS AND METHODS: Spirometry was used to measure maximal inspiratory mouth pressure (P(IMAX)), which was calculated by using the lung residual volume and maximal respiratory pressures at the mouth (P(EMAX)), 2 days before and again 30 days after kidney transplantation in 26 patients with ESRD. PIMAX and PEMAX values less than 60% of the predicted value were considered abnormal. RESULTS: Mean ± SD PIMAX values showed significant increase from 31.88 ± 8.58 cmH2O before kidney transplantation to 37.65 ± 13.39 cmH2O after transplant (P < 0.001). Similarly, a significant increase in PEMAX values was observed from 33.04 ± 16.12 cmH2O to 39.19 ± 20.34 cmH2O (P < 0.001). Nineteen patients (73.1%) showed significant increases in PIMAX and PEMAX values. Mean serum creatinine decreased from 6.94 to 1.32 (P < 0.001) after transplant. CONCLUSION: Although both PIMAX and PEMAX values increased significantly after kidney transplant, these measurements were still below lower limit of normal. This suggests that factors other than uremic myopathy may contribute to respiratory muscle weakness in patients CKD.